O Dasein-Autista: um olhar através das filosofias de Ludwig Wittgenstein e Martin Heidegger - Barros, Maressa Pinheiro (2022)
The term autism was introduced by Eugen Bleuler (1857-1939) in 1911, a Swiss psychiatrist who used the name to describe schizophrenic patients who seemed disconnected from the outside world. Since then, the term has been given new meanings and among them, the autistic psychopathy, described in 1944 by the Austrian physician Hans Asperger (1906-1980), having its name linked to the denomination of the mildest level of autism until 2015 with the publication of the Diagnostic and Statistical Manual of Mental Disorders – 5 (DSM-5). According to the medical literature, the DSM-5 considers the main criteria for designating the term autism, constant deficits in communication and social interaction. Therefore, the present work seeks to elucidate the autistic person beyond terms, prejudices, historical context and medical designations. Based on the study, through the exegetical method, the philosophy expressed in the book Philosophical Investigations (2014) by the Austrian Ludwig Wittgenstein (1889-1951) and the work Being and Time (1927) by the German philosopher Martin Heidegger (1889-1976), with their respective concepts of Grammar, Rules, Following Rules, Ways of Life, Language Games, Dasein, Historicity, Temporality, Being-in-the-World. It sought to demonstrate through language and hermeneutic phenomenology, the existing problem in the practice of reducing the human to terms and diagnoses, announcing, consequently, the urgency of breaking with capacitism and the search for validation of a human ideal or a human utility